Pengaruh Modal Intelektual terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Intervening pada Perusahaan Manafaktur yang Terdaftar di BEI Periode 2018-2020 - Komang Wiryawati; Rizal Rinofah; Alfiatul Maulida (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Intellectual capital is an intangible asset in the form of information resources and knowledge that serves to improve competitiveness and increase company performance. The purpose of this study is to determine the influence of intellectual capital on firm value with financial performance as an intervening variable in manufacturing companies listed on the IDX for the 2018-2020 period. This research is quantitative in nature by taking 126 samples from companies listed on the IDX for the 2018-2020 period. Intellectual capital is measured by value added intellectual coefficient (VAIC™), firm value is measured using price to book (PBV), and financial performance is measured by return on asset (ROA) ratio. The sampling method in this study was carried out by purposive sampling technique. The analytical methods used in this study are descriptive statistical tests, classical assumption tests, mediation tests and multiple linear regression equations using the IBM SSPS application. The results of this study indicate that intellectual capital has a positive and significant effect on financial performance, intellectual capital has a positive and significant effect on firm value, financial performance has a positive and significant effect on firm value, and intellectual capital has a positive and significant effect on firm value through financial performance as a variable. intervention. Keywords: Intellectual Capital; Financial Performance; Firm Value